2015
DOI: 10.2196/mhealth.3505
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Physical Activity Tracking via Android Smartphones Compared to ActiGraph Accelerometer: Laboratory-Based and Free-Living Validation Studies

Abstract: BackgroundThere is increasing interest in using smartphones as stand-alone physical activity monitors via their built-in accelerometers, but there is presently limited data on the validity of this approach.ObjectiveThe purpose of this work was to determine the validity and reliability of 3 Android smartphones for measuring physical activity among midlife and older adults.MethodsA laboratory (study 1) and a free-living (study 2) protocol were conducted. In study 1, individuals engaged in prescribed activities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 30 publications
7
87
0
2
Order By: Relevance
“…Many commercially available products, such as FitBit and Jawbone, use accelerometers in a similar way to allow people to track their own day-and nighttime activity. 6 Several commercial algorithms have been developed that translate human acceleration data into useful activity-level and wake-rest information after verification with PSG data. 7,8 Recent patient studies have used accelerometer data from traumatic brain injury (TBI) patients to document persistent sleep disturbances days and years after mild-to-moderate TBI, with longer 24-h sleep durations, increased nighttime sleep interruptions, and more daytime drowsiness.…”
Section: Introductionmentioning
confidence: 99%
“…Many commercially available products, such as FitBit and Jawbone, use accelerometers in a similar way to allow people to track their own day-and nighttime activity. 6 Several commercial algorithms have been developed that translate human acceleration data into useful activity-level and wake-rest information after verification with PSG data. 7,8 Recent patient studies have used accelerometer data from traumatic brain injury (TBI) patients to document persistent sleep disturbances days and years after mild-to-moderate TBI, with longer 24-h sleep durations, increased nighttime sleep interruptions, and more daytime drowsiness.…”
Section: Introductionmentioning
confidence: 99%
“…2). Recent research has further demonstrated that smartphones provide accurate steps counts 22 and reliable activity estimates in both laboratory and free-living settings 23 . We perform complete-case analyses, which we accompany with sample-correction, stratification, outlier, and balance testing to verify that our conclusions are robust to missing data (see Supplementary Table 1) and biases in age and gender, and hold for both high and middle income countries (see Methods and Extended Data Figs.…”
mentioning
confidence: 99%
“…Thresholds for sedentary behavior (<50.92 counts/minute) and moderate-vigorous physical activity (>305.36 counts/minute) were used from a validation study of Android devices. [17] Two authors (TS and RW) first independently analyzed participant feedback to look for common themes and then met and agreed upon common themes.…”
Section: Discussionmentioning
confidence: 99%